Pengaruh Penambahan Konsentrasi CMC dan Gliserol pada Larutan Edible Coating Gel Lidah Buaya (Aloe vera L.) Terhadap Mutu Buah Nanas (Ananas comosus) - Nisrina Mufidah; Narwati Narwati; Bambang Sunarko; Ferry Kriswandana (FORIKES, 2022)
Pineapple is a fruit that contains many nutrients so it is good for consumption. To consume pineapple, it takes a long time to peel the skin, thus encouraging innovation to sell fresh pineapple in the form of sliced pineapple. Pineapple that is peeled more quickly loses quality. This can be prevented with edible coating of aloe vera. This research was conducted to determine the effect of aloe vera edible coating with the addition of CMC and glycerol, on the moisture content, weight loss, and organoleptic (color, texture, aroma, taste) of sliced pineapple. This research was a true experimental type with pretest-posttest with control group design. Variations in concentration of CMC (1%, 1.5%) and glycerol (0.5%, 1%) and were replicated 4 times so that there were 24 samples. Observational data including moisture content, weight loss, and organoleptic (color, texture, aroma, taste) were analyzed using the One Way ANOVA test. Until the 9th day of storage, the smallest decrease in water content was found in the G2C2 treatment, which was 84.04%. The smallest increase in weight loss was also found in the G2C2 treatment, which was 11.11%. The highest average organoleptic score on the parameters of color, aroma, texture, and taste was the G2C2 treatment. The provision of aloe vera edible coating on pineapple affects the water content, weight loss and organoleptic properties including color, aroma, texture and taste. The addition of CMC and glycerol concentrations affected the water content, weight loss, color, aroma, and texture but did not affect the taste of pineapple during storage. To improve the results of this study, it is necessary to carry out further research by examining the effect of giving aloe vera edible coating with the addition of CMC and glycerol on total dissolved solids and pH.Keywords: edible coating; Aloe vera; pineapple ABSTRAK Nanas merupakan buah yang mengandung banyak nutrisi sehingga baik dikonsumsi. Untuk mengonsumsi nanas, memerlukan waktu lama dalam pengupasan kulitnya, sehingga mendorong inovasi untuk menjual nanas segar dalam bentuk nanas potong. Nanas yang dikupas lebih cepat mengalami penurunan mutu. Hal tersebut dapat dicegah dengan edible coating dari lidah buaya. Penelitian ini dilakukan untuk mengetahui pengaruh pemberian edible coating lidah buaya dengan penambahan CMC dan gliserol, terhadap kadar air, susut bobot, dan organoleptik (warna, tekstur, aroma, rasa) nanas potong. Penelitian ini berjenis eksperimen murni dengan pretest-posttest with control group design. Variasi konsentrasi CMC (1%, 1,5%) dan gliserol (0,5%, 1%) dan dilakukan replikasi sebanyak 4 kali sehingga berjumlah 24 sampel. Data hasil pengamatan meliputi kadar air, susut bobot, dan organoleptik (warna, tekstur, aroma, rasa) dianalisis menggunakan uji One Way ANOVA. Hingga penyimpanan hari ke 9, penurunan kadar air terkecil terdapat pada perlakuan G2C2 yaitu sebesar 84,04%. Peningkatan susut bobot terkecil juga terdapat pada perlakuan G2C2 yaitu sebesar 11,11%. Rerata skor organoleptik tertinggi pada parameter warna, aroma, tekstur, dan rasa adalah perlakuan G2C2. Pemberian edible coating lidah buaya pada buah nanas berpengaruh terhadap kadar air, susut bobot dan organoleptik meliputi warna, aroma, tekstur dan rasa. Penambahan konsentrasi CMC dan gliserol berpengaruh terhadap kadar air, susut bobot, warna, aroma, dan tekstur namun tidak berpengaruh terhadap rasa buah nanas selama penyimpanan. Untuk menyempurnakan hasil penelitian ini, perlu dilakukan penelitian lanjutan dengan mengkaji pengaruh pemberian edible coating lidah buaya dengan penambahan CMC serta gliserol terhadap total padatan terlarut dan pH.Kata kunci: edible coating; lidah buaya; nanas